Induction FOLFIRINOX for patients with locally unresectable pancreatic ductal adenocarcinoma. Issue 3 (31st October 2021) - McIntyre, Caitlin A.; Cohen, Noah A.; Goldman, Debra A.; Gonen, Mithat; Sadot, Eran; O'Reilly, Eileen M.; Varghese, Anna M.; Yu, Kenneth H.; Balachandran, Vinod P.; Soares, Kevin C.; D'Angelica, Michael I.; Drebin, Jeffrey A.; et al.
Abstract: Objectives: Patients with locally advanced pancreatic adenocarcinoma (PDAC) receive induction chemotherapy with or without radiation, with the goal of R0 resection and improving survival. Herein, we evaluate the outcomes of patients who presented with Stage III PDAC and received induction FOLFIRINOX. Methods: An institutional database was queried for consecutive patients who received induction FOLFIRINOX for locally unresectable PDAC between 2010 and 2016. Clinical and radiographic parameters were assessed pre‐ and posttreatment, and clinical outcomes were evaluated. Results: There were 200 patients who met the inclusion criteria. The median number of cycles of FOLFIRINOX was 8, 70% ( n = 140) received radiation, and 18% ( n = 36) underwent resection. Median overall survival (OS) in resected patients was 36 months (95% confidence interval [CI]: 24–56), and this group had improved OS compared to patients that did not undergo resection (hazard ratio (95% CI): 0.41 (0.26–0.64), p < 0.001). Patients ( n = 112) who did not progress on induction therapy but remained unresectable had a median OS of 23.9 months (95% CI: 21.1–25.4). Conclusion: Nearly 20% of patients with locally advanced PDAC responded sufficiently to induction FOLFIRINOX to undergo resection, which was associated with improved OS compared to patients that did not undergo resection. Patients with stable disease who remain unresectable represent a group of patients with locally advanced PDAC who may benefit from optimization of additional nonoperative treatment.